Public-Private Partnerships and Their Limiting Factors for a Sustainable Public Sewerage Industry: A Comparative Analysis of Three Municipal Cases in Japan - Fujiwara, Naoki (Universidad Estatal a Distancia, Costa Rica, 2021)
This study focuses on the conditions for the implementation of the APP, in the form of a concession for the management of the sewerage business. Three uncertainties were identified as limiting factors for PPPs; a) level of service to ensure sustainability, aging of machinery and equipment; b) public spending on rain and the national government subsidy system; c) residents' perception of the water business and the provision of equitable services. The methodology includes case studies (cities of Hamamatsu, Osaka and Nara in Japan). It consists of two parts: a) analysis of relevant published materials and b) application of surveys and semi-structured interviews with municipal officials and, in the case of Osaka, an affiliated company established to operate the sewer business.